The Decision Support System In Determining Appropriation Of Permanent Employee Appointment Using Analytic Hieararchy Process (AHP) Method At Gerai 212 Mart - Handika, Elsi; Sari , Herlina Latipa; Prahasti, Prahasti (LPPJPHKI Universitas Dehasen Bengkulu, 2022)
Employee performance assessment aims to find potential employees who have profiles that match the criteria of loyalty, performance and responsibility. Another problem that occurs is the difficulty of selecting employees properly and fairly due to the diversity of educational backgrounds, experiences, competencies and employee portfolios so that it becomes a concern for Gerai 212 Mart in determining whether or not employees are eligible to serve as permanent employees. To overcome these obstacles, a decision support system is needed using the Analytical Hierarchy Process (AHP) method to be used as a supporting medium in supporting the decision-making process. Analytical Hierarchy Process (AHP) method which has the ability to measure the performance of decision alternatives in a simple mathematical form. The application is built using the Visual Basic 2010 programming language and the method used in this research is the waterfall method. From the results of the tests carried out, it can be concluded that the assessment for being appointed as permanent employees can be done well by taking the number of employees with the highest value of 0.2605 and the lowest value of 0.1053.